2008
DOI: 10.1007/s11240-008-9390-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TDZ and 2, 4-D on peanut somatic embryogenesis and in vitro bud development

Abstract: Failure of peanut somatic embryos to convert into plantlets is attributed to the abnormal development of the plumule. Thidiazuron (TDZ) was effective in the conversion of peanut somatic embryos to plantlets by triggering morphogenetic activity in the abnormal plumules of the rooted somatic embryos. The present study aimed to induce normal embryo differentiation by culturing the embryogenic masses in embryo development medium containing 2,4-D and various concentrations of TDZ. Although this was not achieved due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 13 publications
0
8
1
Order By: Relevance
“…A successful regeneration of the subdivided rosettes from TDZ was observed when they were transferred to MS culture media without growth regulators, showing that subcultivation in these conditions is crucial for later development of these explants (Khalafalla and Hattori, 1999;Joshi et al, 2008). Although Prathanturarug et al (2005) has suggest that a second treatment with TDZ may increase culture multiplication, the results from our work do not corroborate with this possibility, since explants regeneration in culture media supplemented with high doses of TDZ was very low.…”
Section: Cultured In Vitrocontrasting
confidence: 55%
See 1 more Smart Citation
“…A successful regeneration of the subdivided rosettes from TDZ was observed when they were transferred to MS culture media without growth regulators, showing that subcultivation in these conditions is crucial for later development of these explants (Khalafalla and Hattori, 1999;Joshi et al, 2008). Although Prathanturarug et al (2005) has suggest that a second treatment with TDZ may increase culture multiplication, the results from our work do not corroborate with this possibility, since explants regeneration in culture media supplemented with high doses of TDZ was very low.…”
Section: Cultured In Vitrocontrasting
confidence: 55%
“…Low concentrations of TDZ were effective in inducing multiple in vitro shoots in peanuts cultures (Joshi et al, 2008). In Lens culinaris Medik., 0.5 µM TDZ also stimulate in vitro shoots formation (Chhabra et al, 2008).…”
Section: Cultured In Vitromentioning
confidence: 99%
“…However, later studies have demonstrated that TDZ, unlike traditional cytokinins, is capable of fulfilling both the cytokinin and auxin requirements of various regenerative responses of many different plant species Hutchinson et al 1996;Murthy et al 1998;Sanikhani et al 2006). Although TDZ has not been used in regeneration of petunia, it has proven to be highly efficient for shoot regeneration in various plant species (Akasaka et al 2000;Sharma et al 2007;Dimech et al 2007;Yucesan et al 2007;Joshi et al 2008;Liu and Pijut 2008;Corredoira et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In Arachis hypogaea a good embryo conversion to plantlets was recorded at 0.18 M sucrose and 9.08 lM TDZ. This combination triggered the morphogenetic activity in the plumule that was not observed when other combinations were used (Joshi et al 2008).…”
Section: Discussionmentioning
confidence: 88%